Analisis strategi pemasaran untuk meningkatkan daya saing UMKM ladu arai pinang ikhlas di gasan gadang - ., Arivetullatif; ., Sulastri (CV. ITTC INDONESIA, 2024)
The Marketing strategies is one of way to win a sustainable competitive advantageboth for companies that produces goods or services. The Marketing startegies can use as a basic in order to preparing of the companies planning. One of the problems that still often occurs today is UMKM competition which is getting tougher because UMKM are an indicator of the success of a nation’s development. This is indicated by the many findings of problems that occur in UMKM at this time. In the case, the government’s role is expected to create UMKM that have quality and creativity to be able to compate with other UMKM. This study aims to: (1) Increase sales of ladu arai pinang nut in Gasan Gadang: (2) To find out how to improve the competitiveness of UMKM in Ladu Arai Pinang in Gasan Gadang. This study uses qualitative research, data collection techniques are carried out through observation, interviews and documentation. Consists of primary data and secondary data. The results of the study show that the results of this study indicate that UMKM in the Gasan Gadang area, Padang Pariaman Regency, still have many internal or external problems. The problem that often occurs is the lack of costs for business capital and the distribution of goods that are not appropriate are not in accordance with the target. Many UMKM actors are walking in the place in developing their business because they lack innovation, such as innovation in taste and packiaging, umkm actors must be literate with technology. This Is one of the keys to the success of business. Before starting a bisiness, one must have a clear vision and mission so that a business can be directed according to the target to be achieved. The role of the government is also very important because UMKM are one of the indicators of the success of a nation.